(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Early childhood education plays a critical role in laying the foundation for lifelong learning and development. This paper explores innovative technology-based approaches to organizing integrated classrooms in preschool groups. By using digital tools, flexible learning platforms, and interactive resources, teachers can create dynamic and inclusive learning environments that meet the diverse needs of young learners. This paper explores the benefits, challenges, and best practices of integrating technology into early childhood settings to improve learning outcomes and promote holistic development.